2014
DOI: 10.1142/s0217732314501235
|View full text |Cite
|
Sign up to set email alerts
|

The remnants in Reissner–Nordström–de Sitter quintessence black hole

Abstract: According to the effects of quantum gravity, we investigated the fermion tunneling from the Reissner–Nordström–de Sitter quintessence (RN–dSQ) black hole. The corrected temperature is not only determined by the mass and charge of the black hole, but also depended on the quantum number of the emitted fermion and β, which is a small value representing the effects of quantum gravity. The effects of quantum gravity slowed down the increase of the temperature and led to the remnants of the black hole. We think it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…When b → ∞, the metric (7) reduce to Reissner-Nordström-de Sitter black hole; When L 2 → ∞ , it get a the black hole, which surrounded by quintessence; When b → ∞ and L 2 → ∞ , metric (7) becomes to the Reissner-Nordström (R-N) black hole [34,35]. Consider the the scalar perturbation field, the massless Klein-Gordon equation in a general background spacetime is given by…”
Section: Quasinormal Modes Of Scalar Field In the Rn-dsq Black Holementioning
confidence: 99%
See 1 more Smart Citation
“…When b → ∞, the metric (7) reduce to Reissner-Nordström-de Sitter black hole; When L 2 → ∞ , it get a the black hole, which surrounded by quintessence; When b → ∞ and L 2 → ∞ , metric (7) becomes to the Reissner-Nordström (R-N) black hole [34,35]. Consider the the scalar perturbation field, the massless Klein-Gordon equation in a general background spacetime is given by…”
Section: Quasinormal Modes Of Scalar Field In the Rn-dsq Black Holementioning
confidence: 99%
“…In [34], considering the quintessence energy, the authors got the Reissner-Nordström-de Sitter quintessence (RN-dSQ) black hole. In the previous work, people have discussed the thermodynamics of RN-dSQ black hole [35]. The result showed that the thermodynamic proper of the black hole is related to the quintessence and the cosmological constant.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, significant attention has been devoted to a discussion of static spherically symmetric black hole solutions surrounded by quintessence matter and their properties [5][6][7][8][9][10]. Also, several extensions of the Kiselev solutions [5] have been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the applications of quantum gravity have been widely studied. In particular, the quantum gravity can modify 2 Advances in High Energy Physics the thermodynamics of black hole, such as Schwarzschild-Tangherlini black hole [18,19] and Reissner Nordstrom de Sitter quintessence black hole [20,21], and the strength of the quantum gravitational effect can be constrained by the gravitational wave events [22].…”
Section: Introductionmentioning
confidence: 99%